Tectonic and Eustatic Signatures in Depositional Sequences of a Foreland Basin: Example from the Oligo-Miocene Asmari Formation of Southwest Iran - Amin-Rasouli, Hadi (Sulaimani Journal for Pure and Applied Sciences, 2016)
The Oligo-Miocene Asmari Formation (up to 500 m) and its time- equivalents in the Persian Gulf foreland basin are one of the world’s most important petroleum reservoirs in southwest Iran. It is unconformably underlain by the basinal deposits of the Eocene-Oligocene Pabdeh Formation and is unconformably overlain by the continental deposits of the Middle Miocene Gachsaran Formation. Field and petrographic investigations of 10 outcrop and subsurface sections of the Asmari Formation in the northwest of the basin led to recognition of dominantly shallow marine carbonate, siliciclastic and evaporate facies. These are arranged into 7 depositional sequences that are correlated with the Oligo- Miocene eustatic sea-level cycles. In the southwest distal sections, the lower and middle Asmari sequences (Chattian-Aquitanian) consist of mixed carbonate and siliciclastic facies, which change laterally to pure carbonate or carbonate and evaporate facies in the proximal area to the northeast. These sequences are absent towards the Zagros thrust belt, where the dominantly carbonate facies of the upper Asmari (Burdigalian) unconformably overlies the Eocene Shahbazan Formation. Both eustatic sea-level changes and regional tectonics were responsible in controlling lateral and vertical facies variations of the Asmari succession. The predominantly carbonate facies and correlation of Asmari sequences with global sea-level cycles suggest a strong eustatic control during deposition. Siliciclastic intervals in the mixed siliciclastic-carbonate deposits are interpreted to represent forebulge uplift as a result of tectonic loading of the thrust sheets. The shallow marine pure carbonate/carbonate- evaporate intervals that cover the proximal foredeep or the entire foreland basin appear to be the consequence of both eustatic sea-level changes and tectonic quiescence.
Keywords: Asmari; Facies,Sequence stratigraphy,Tectonic event,Depositioalenvironment